BigPsy: a big data framework to support psycho-informatics - Muizz, Rashik Al; Uddin, Md. Sakib; Sakib, Mirza Md. Nazmus; Islam, S.M.Fahmidul; Ahmed, Nourin (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.